National/European identities and political alignments. (June 2021) - Dalton, Russell J
Reflecting on the articles in this special issue of European Union Politics, this essay first asks whether EU scholarship has sufficiently conceptualized and measured what it means to identify with the European Project and/or the European Community. The evidence in this special issue indicates that many citizens now have attachments to Europe, albeit in uncertain depth. European attachments also exist in combination with or as an alternative to national identities. European/national identities also now overlap with partisan attachments, potentially forming a new basis of political cleavage. The research in this collection demonstrates a rich portfolio of methods to examine this important topic, and yields new evidence of how geographic identities are related to public opinion on issues such as immigration.